Research on levitation coupled with standing wave levitation and electromagnetic levitation - Jiao, Xiao Yang (Strojniški vestnik, 2013)
In order to solve the problem caused by metal materials' inability to be cooled without contact with other materials after being heated by electromagnetic levitation, a new method is proposed: using a standing wave levitator to levitate the melted metal. The standing wave levitator adopts a concave spherical surface on the emitter and the reflector. Using ANSYS software, the transducer and the standing wave fields were simulated. Based on the simulation, the distribution and the maximum acoustic pressure with different radii of the concave spherical surface on the emitter and the reflector can be obtained, from which the optimal radius was determined. Based on the optimisation, a prototype of a standing wave levitation device was designed and manufactured. Levitation experiments for light and heavy specimens were carried out. It is shown that steel balls can be levitated stably when the distance between the emitter and the reflector is two times that of the wavelength. Next, the standing wave levitator was used in an attempt to levitate a steel ball of 5 mm in diameter after being non-contact heated by electromagnetic levitation. The results show that the method utilising a standing wave levitator to levitate and cool the metal materials after being non-contact heated by the electromagnetic levitation is feasible at this preliminary state.
Keywords: ANSYS simulation; brezkontaktno hlajenje; electromagnetic levitation; elektromagnetna levitacija; levitacija na stojno valovanje; non-contact cooling; simulacija ANSYS; standing wave levitation